THE ASSESSMENT OF KNOWLEDGE AND PRACTICE REGARDING POST-OPERATIVE CARE OF CARDIAC CATHETERIZATION AMONG NURSES - MURSLEEN , IU; SADDIQUE , H; TASNEEM , SS (Biological and Clinical Sciences Research Journal, 2024)
Post-operative care following cardiac catheterization is a critical component of patient management, significantly influencing recovery outcomes and preventing complications. Nurses play a pivotal role in ensuring the effectiveness of this care. This study aimed to assess the knowledge and practices of ICU nurses regarding post-operative care of cardiac catheterization patients in tertiary care hospitals in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 150 nurses selected using convenience sampling. Data were collected using a structured and validated questionnaire that assessed demographic characteristics, knowledge, and practices related to post-operative care. Statistical analysis was performed using SPSS version 26, including descriptive and inferential statistics to identify trends and associations. Results: The majority of nurses (60.7%) correctly identified the timing for serum creatinine testing post-procedure, but only 33.3% recognized signs of pseudoaneurysm. Practices such as proper patient positioning (36.7%) and ECG monitoring (48.0%) were inconsistently followed. Significant associations were observed between education level, years of experience, and competency levels (p < 0.05). However, infection prevention measures were poorly adhered to, with only 13.7% following recommended protocols. Conclusion: The study highlights critical gaps in the knowledge and practices of ICU nurses regarding post-operative care for cardiac catheterization patients. Targeted training programs, policy interventions, and adherence to evidence-based practices are essential to address these deficiencies and improve patient outcomes in ICU settings.